PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED INSTRUCTION (PBI) PADA MATERI SISTEM KOORDINASI SISWA SMA KELAS XI - Desi Ratnasari; Handoko Santoso; Widya Sartika Sulistiani (EDUBIOLOCK, 2021)
This development aims to produce a Problem-Based Instruction-based Student worksheet product that is suitable for use as a learning resource for class XI SMA. The development of the Student worksheet using 4-D procedures and models suggested by Thiagrajan, Semmel, and Semmel consists of 4 development stages, namely: Define, Design, Develop, and Disseminate. The stages carried out in this research are only up to the third stage, namely Develop, this is due to time and cost limitations. The process for producing this Student worksheet begins with the Student worksheet validation stage by 2 material experts and 2 design experts. This Student worksheet was also tested at school to see user responses, namely the biology subject teacher and 10 students of SMA N 1 Purbolinggo. The results of this analysis are to determine the feasibility level of developing a Student worksheet as a biology teaching material based on the evaluation of the results of the Student worksheet design validation which obtained a percentage value of 89%, the evaluation of the results of material validation in the Student worksheet obtained a percentage value of 97%, the assessment of the results of the validation of the biology subject teacher obtained a percentage value of 88. % and the student response test obtained a percentage value of 94%. Based on the data from the test results of experts, teachers, and students, an average total score of 92% or in the criteria of "Very Good" is obtained, and it can be concluded that the developed problem-based biology Student worksheet has met the minimum eligibility requirements. 75%, so it is feasible to be used as a reference for biology teaching materials in the coordination system material.